2021
DOI: 10.3390/math9101076
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Novel Fuzzy Evaluation Model by One-Sided Specification Capability Indices

Abstract: When all of the one-sided specification indices of each quality characteristic reach the requirements of the process quality level, they can ensure that the process capability of the product meets the requirements of the process quality level. This study constructs a fuzzy membership function based on the upper confidence limit of the index, derives the fuzzy critical value, and then labels the fuzzy critical value on the axis of the visualized radar chart as well as connects adjacent critical points to shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…(2) The quality evaluation radar chart offers a quality evaluation method for products with multiple quality characteristics and a selection tool for suppliers. It allows machine-tool manufacturers and suppliers to evaluate the standard of all quality characteristics at the same time and make process improvements in quality characteristics with poor quality levels [39,40]. (3) When directly comparing the estimated value of the index with the minimum value, M V is employed to determine whether the quality level meets the requirements, which is more in line with its practical use [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) The quality evaluation radar chart offers a quality evaluation method for products with multiple quality characteristics and a selection tool for suppliers. It allows machine-tool manufacturers and suppliers to evaluate the standard of all quality characteristics at the same time and make process improvements in quality characteristics with poor quality levels [39,40]. (3) When directly comparing the estimated value of the index with the minimum value, M V is employed to determine whether the quality level meets the requirements, which is more in line with its practical use [35].…”
Section: Discussionmentioning
confidence: 99%
“…As can be observed from Figure 2, and based on Equations ( 38) and ( 39), the statistical testing rules can be stated with the following conditions: 0 pmh the s suppliers and marked them on the pentagonal radar chart with 5 a  , as follows. As can be observed from Figure 2, and based on Equations ( 38) and (39), the statistical testing rules can be stated with the following conditions:…”
Section: Establishing Supplier Selection Rules Based On M V and The R...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a large number of studies have also suggested that the radar chart is a visual 2D plan, which is a practical graphical analysis and management tool with high readability and a wide range of applications, including engineering, education, management, etc. [19][20][21][22][23][24][25][26][27]. The radar chart can evaluate the performance of all workstations at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies related to process quality have pointed out that enhancing process quality can increase product lifetime as well as reduce the rate of process scrap and rework. Not only can it raise the value of the product, but it also can contribute to the sustainable development of enterprises in the face of challenges to global warming [7,10,17]. Numerous studies have stated that under the thinking of circular economy and sharing economy, good product quality, high availability, and long lifetime can not only reduce operating costs but also improve operating efficiency, thereby enhancing users' satisfaction and willingness [18,20,24].…”
Section: Introductionmentioning
confidence: 99%